Present Remotely

Send the link below via email or IM

• Invited audience members will follow you as you navigate and present
• People invited to a presentation do not need a Prezi account
• This link expires 10 minutes after you close the presentation

Do you really want to delete this prezi?

Neither you, nor the coeditors you shared it with will be able to recover it again.

Steps for Solving

No description
by

William Stremple

on 30 October 2013

Report abuse

Transcript of Steps for Solving

a Multi-step Equation
Mr. Stremple
1. Distribute
Steps for Solving
3. Isolate the variable term by addition or subtraction
4. Isolate the variable by multiplication or division
2. Combine Like Terms
4(2x+3)-3=97
1. Distribute
4 ( 2x + 3 ) - 3 = 97
4(2x) + 4(3) - 3 = 97
8x + 12 - 3 = 97
2. Combine Like Terms
4 ( 2x + 3 ) - 3 = 97
4(2x) + 4(3) - 3 = 97
8x + 12 - 3 = 97
8x + 9 = 97
3. Isolate the variable term by addition or subtraction
4 ( 2x + 3 ) - 3 = 97
4(2x) + 4(3) - 3 = 97
8x + 12 - 3 = 97
8x + 9 = 97
-9 -9
8x = 88
4. Isolate the variable by multiplication or division
4 ( 2x + 3 ) - 3 = 97
4(2x) + 4(3) - 3 = 97
8x + 12 - 3 = 97
8x + 9 = 97
-9 -9
8x = 88
--- ----
8 8
x = 11
Distributing
You distribute when there is a number or variable outside of a parenthesis that has operations inside. You need to multiply the number outside by EVERYTHING inside.

EX: 7 (4x - 6)
7(4x) - 7(6)
28x - 42
Like Terms
Like terms are any term (part of an expression or equation) that are similar.

EX: 2x + 4 - 12
4 and -12 are like terms
EX: 3x - 5x + y
3x and -5x are like terms
Isolate the variable term
In this step we use the opposite operation to get our variable term alone on side of the equation.

EX: If the equation says you are adding, subtract to get rid of it.
4x + 8 = 17
-8 -8
Isolate the variable
In this step we are using the opposite operation to get the variable by itself and finally solve the equation.

EX: x/4 = 22
*4 *4
x = 88
Check
After getting an answer, always check it by substituting into the original equation.
4 ( 2x + 3 ) - 3 = 97
4 [2(11) + 3] - 3 = 97
4 [22 + 3] - 3 = 97
4[25] - 3 = 97
100 - 3 = 97
97 = 97
Full transcript